1996
DOI: 10.1128/mcb.16.9.4798
|View full text |Cite
|
Sign up to set email alerts
|

Single-Stranded-DNA Binding Alters Human Replication Protein A Structure and Facilitates Interaction with DNA-Dependent Protein Kinase

Abstract: Human replication protein A (hRPA) is an essential single-stranded-DNA-binding protein that stimulates the activities of multiple DNA replication and repair proteins through physical interaction. To understand DNA binding and its role in hRPA heterologous interaction, we examined the physical structure of hRPA complexes with single-stranded DNA (ssDNA) by scanning transmission electron microscopy. Recent biochemical studies have shown that hRPA combines with ssDNA in at least two binding modes: by interacting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
123
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 60 publications
13
123
1
Order By: Relevance
“…It is likely that a mutation at the zincfinger domain inhibits the conformational change in p70 that is necessary for the switch from an unstable and weak RPA-ssDNA interaction to a stable and strong RPA-ssDNA interaction. This is also supported by recent biochemical studies [29], which indicate that human RPA combines with ssDNA in at least two binding modes : one is a relatively unstable and compact complex and the other is an elongated and stable complex.…”
Section: Figure 4 Zinc-finger Domain Of Rpa Is Not Involved In Its Stsupporting
confidence: 77%
See 3 more Smart Citations
“…It is likely that a mutation at the zincfinger domain inhibits the conformational change in p70 that is necessary for the switch from an unstable and weak RPA-ssDNA interaction to a stable and strong RPA-ssDNA interaction. This is also supported by recent biochemical studies [29], which indicate that human RPA combines with ssDNA in at least two binding modes : one is a relatively unstable and compact complex and the other is an elongated and stable complex.…”
Section: Figure 4 Zinc-finger Domain Of Rpa Is Not Involved In Its Stsupporting
confidence: 77%
“…Upon DNA binding, the structural change in p70 allows p34 (and its phosphorylation sites) access to DNA-PK for phosphorylation. In keeping with this notion, others have shown that formation of the extended hRPA30nt complex, the stable form of RPA-DNA interaction, correlates with increased phosphorylation of RPA p34 [29]. In this way, the phosphorylation of p34 by DNA-PK is controlled by the p70 subunit in a zinc-fingerdomain dependent manner.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Two binding modes have been identified: an intermediate and relatively weak binding mode, characterized by an occluded binding site of 8 -10 nucleotides (8), and a more stable binding mode in which RPA covers ϳ30 nucleotides (7,9,10). Single-stranded DNA covered by RPA remains in an extended conformation under low ionic strength conditions, but more physiological salt concentrations induce a severe compaction of RPA⅐DNA complexes (11), which may reflect yet another DNA-binding mode possibly including 90 nucleotides of bound DNA, as first suggested by work with yeast RPA (12).…”
mentioning
confidence: 99%